ESG, Ownership Structure, and Firm Performance: Evidence from Indonesia - Febriann Dedy Syahputra; Noer Azam Achsani; Linda Karlina Sari (Universitas Negeri Semarang, 2026)
Understanding how firms sustain performance under heightened uncertainty remains a prior issue in corporate finance, particularly in emerging markets characterized by institutional constraints. This study examines the effects of Environmental, Social, and Governance performance, ownership structure, and the COVID-19 crisis on firm performance in Indonesia. This study uses panel data of 39 ESG-committed listed firms over the period 2015–2024, the analysis applies static panel regression and dynamic Difference Generalized Method of Moments to address endogeneity and unobserved heterogeneity. This study shows that Environmental, Social, and Governance performance is positively associated with firm performance in Indonesia. The mean difference tests and scatter plot analysis indicate that firms with higher ESG engagement tend to exhibit higher return on assets and greater performance stability, particularly during the COVID-19 period. These patterns are confirmed by the dynamic GMM results, which reveal a positive and statistically significant effect of ESG performance on return on assets after accounting for endogeneity. The GMM estimates further show that liquidity and firm size positively influence asset-based profitability, while the COVID-19 shock exerts a negative effect on firm performance. Overall, the findings suggest that ESG integration enhances operational efficiency and functions as an effective risk-mitigation mechanism, underscoring the importance of embedding sustainability into core business strategies and strengthening ESG-related policy frameworks in emerging markets.